2022
DOI: 10.1007/s10826-021-02206-9
|View full text |Cite
|
Sign up to set email alerts
|

Family Context and ADHD Symptoms in Middle Childhood: an Explanatory Model

Abstract: Recent research suggests that Attention Deficit Hyperactivity Disorder (ADHD) may be influenced by interactions between the individual and their social context. This study examined the predictive value of family context variables and attentional control levels on child ADHD symptoms. A new explanatory model of the relationship amongst these variables was also tested. A sample of 754 families with children aged 7 to 11 was assessed through the Conners Parent Rating Scale, the Haezi-Etxadi Family Assessment Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Perhaps we have not been able to capture the relationship between executive functions and family functioning style in the group of children with ADHD because, in the case of higher-order cognitive functions, there are other, more important factors modeling this influence that have not been investigated in this study. Contrary to the approach of other researchers who focused on selected cognitive skills ( Barreto-Zarza et al, 2022 ; Forssman et al, 2012 ; Kofler et al, 2017 ), a general index of the quality of executive functioning was used for statistical analysis, consisting of several tests that examined lower-and higher-order executive functions. This may have caused the relationship between the variables in this study to not be shown and may have somewhat blurred the validity of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps we have not been able to capture the relationship between executive functions and family functioning style in the group of children with ADHD because, in the case of higher-order cognitive functions, there are other, more important factors modeling this influence that have not been investigated in this study. Contrary to the approach of other researchers who focused on selected cognitive skills ( Barreto-Zarza et al, 2022 ; Forssman et al, 2012 ; Kofler et al, 2017 ), a general index of the quality of executive functioning was used for statistical analysis, consisting of several tests that examined lower-and higher-order executive functions. This may have caused the relationship between the variables in this study to not be shown and may have somewhat blurred the validity of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence that therapeutic interventions aimed at improving the cognitive functioning of parents of children with ADHD improve the cognitive functioning of the children through better self-regulation of the parent ( Fosco et al, 2018 ). In a Spanish population of children with ADHD in middle childhood ( Barreto-Zarza et al, 2022 ), ADHD symptoms were predictors of better family functioning in terms of social support network, family stress, parental self-efficacy, and attention control. In addition, male sex was also a significant predictor of the intensity of ADHD symptoms, which confirms, in line with the older literature, that male sex is a risk factor for greater severity of ADHD symptoms.…”
Section: Family Disturbances In Adhdmentioning
confidence: 99%
“…Positive parenting and family cohesion promoted wellbeing directly, but also mediated the relationship between ADHD symptom severity and QoL. Family support decreased parental stress, which in turn led to better outcomes for the youth (Barreto-Zarza et al, 2022;Dvorsky & Langberg, 2016). However, social acceptance by both peers and adults seemed to have the greatest impact, buffering ADHD symptom severity, and reducing bullying (Dvorsky & Langberg, 2016).…”
Section: Introductionmentioning
confidence: 98%